Linking Social Capital to Knowledge Productivity An Explorative Study on the Relationship Between Social Capital and Learning in Knowledge-Productive Networks - jong, Tjip.; SpringerLink (Online service) (Houten : Bohn Stafleu van Loghum, 2010)
First in depth study into the relationship between social capital and productivity knowledge.
Introduction: the role of social capital in knowledge-productive networks -- Theoretical exploration: perspectives on social capital, learning and knowledge productivity -- Exploratory case studies: first steps in linking social capital to knowledge productivity -- Conceptual framework: rethinking the link -- Research design: studying knowledge productivity in networks -- Findings: 17 case studies -- Cross case analysis: Relating the empirical findings -- Conclusions and discussion.
Keywords: Social sciences; Social Sciences; Social Sciences, general